The Case for Change & An Ethical Approach to Wellbeing Management in Aviation: Wellbeing II and Advancing an Integrated Health & Safety Culture - Cahill, Joan (My University, 2021)
Work is part of our wellbeing and a key driver of a person’s health. As argued by Elkington (1994), work needs to balance three benefit areas –economic/profit, people/society and planet/ecological(Elkington, 1994)Across different industries -employers are becoming more aware of the financial benefits in relation to supporting and maintaining a healthy work environment and worker wellness. The COVID 19 Pandemic has heighted the need to address wellbeing. Overall, this is changing organisational priorities in terms of addressing wellbeing. At the recent World Economic Forum (2021) –it was reported that 2 out of every 3 employers now have mental health as their no. 1 priority. Further, it was noted that 1 in 6 employees feel supported by their company during COVID. Worker wellness hugely important in safety critical systems such as aviation. Aviation workers need to be fit for duty and aware of risk that compromises their health/wellbeing. Employers (i.e., aviation organisations) have a duty to their employees (i.e., aviation workers). It is expected that they exercise due care by putting in place the necessary protective and preventive measures, to manage risks to health and safety in work.Arguably, the aviation industry defines the concept of worker wellbeing somewhat negatively. Specifically, wellbeing is defined in relation to concepts of ‘fitness for work’ (i.e., avoiding/managing illness) as opposed to(1) keeping well/preventing illnessand (2)thriving/positive wellbeing. Further,the concept is mostly defined from an individual perspective (i.e., defined narrowly). Staff primarily bear the responsibility for beingfit for dutyas opposed to on the organisation. This focus on the individual is particularly acute in relation to aviation workers who are characterized as being at the ‘sharp end’ and having ‘safety critical roles’. This includes pilots, Air Traffic Controllers and Engineers. Largely, this stems from the definition of roles and responsibilities –as defined by the regulator. Overall, aviation organisations primarily have a monitoring role. The role of organisations is to comply with specific monitoring/assessment processes to ensure that staff are well and by implication can perform their duties safety(i.e., fatigue risk, drugs/alcohol testing, aeromedical assessment). In this regard, organisations are required to implement safety management systems –(for example, manage fatigue risk -duty times), but this does not consider the full scope of wellbeing –risks associated with the three pillars of wellbeing (Cahill et al, 2019). Organisations do have a role in providing supports (i.e., health promotion, stress management training, provision of peer support, employee assistance programs) –but this is secondary.Arguably, wellbeing culture is not established within aviation organisations. Research pertaining to airline engagement and attitudes to wellbeing indicates that airlines are not adequately addressing wellbeing risks. In a recent European study investigating safety culture with>7,000 pilots, only 17% of participants reported that their organization cared about their wellbeing, and 21% felt that fatigue was taken seriously within their organization(Reader, Parand and Kirwan, 2016).This issue is now moreurgent given COVID context–increased suffering, job loss etc.This paper reports on the findings oftwo surveys –pertaining to the managementof wellbeingfor aviation workers at both the individual and organisational level. The analysis of survey findings I used to make case for change at different levels. In so doing, a new concept for wellbeing management in aviation wellbeing II –is proposed and described. Potential interventions to support the implementation of Wellbeing II are likely to be multi-component, spanning different socio-technical dimensions (i.e.,training, culture, technology, process design). The paper presents an outline of some possible interventions and associated wellbeing scenarios. The Wellbeing II concept is then discussed. This includes conceptual dimensions of this concept, how it might be managed at an operational and organisational level, and methodologies to further define the Wellbeing II concept. Lastly, some conclusions are drawn.
PUBLISHED
Keywords: Wellbeing; Mental Health; Safety culture; Wellbeing Culture; Workplace wellbeing; Safety II; Safety Management System; Aviation; Stakeholder Evaluation; Human Factors; Sustainable operations; Triple Bottom Line; Smart & Sustainable Planet; Aviation Human Factors; Aviation Safety; COVID 19 Pandemic; Healthy Work; SAFETY MANAGEMENT SYSTEMS; Wellbeing II; work related stress